Study on the Level of Strenght Development in Vocational Training Students - I.M. Butu; G.C. Catuna; A.S. Teodorescu; C.C. Teusdea; I.G. Gheorghe; P. Ivan; A. Ciu (Editura Universitatii Transilvania din Brasov, 2023)
The present work is a study that tracks the level of development of the force of the lower limbs, upper limbs, abdominal muscles but also posterior muscles of the trunk. The research started at the beginning of the current school year and was carried out on the students of the ninth and tenth grades from the Technological High School I. C. Bratianu, from the vocational education. The students from the X-th grade who expressed their agreement to participate in our study were 22, who participated in the 3 modules of school activity in the two hours of physical education weekly. The subjects in the ninth grade who participated in the physical tests were 30 in number.